Economic impact of monetary policy: Focus on real estate sector in Italy. (28th July 2020) - Ahmed, Irfan; Socci, Claudio; Medabesh, Ali; Severini, Francesca; Zotti, Jacopo
Abstract: This study investigates the nexus between financial market and real estate (RE) sector against the backdrop of ECB's unconventional monetary policy. A financial dynamic computable general equilibrium (DCGE) model is calibrated on the financial social accounting matrix (FSAM) of Italian economy. The findings confirm that the inclusion of financial intermediation into real economy affects the real estate sector's output, value added, and pricing.